Bioaugmentation of Atrazine-Contaminated Soil With Paenarthrobacter sp. Strain AT-5 and Its Effect on the Soil Microbiome - Jia, Weibin; Li, Ning; Yang, Tunan; Dai, Weixian; Jiang, Jiandong; Chen, Kai; Xu, Xihui (Frontiers in Microbiology, 2021)
Atrazine, a triazine herbicide, is widely used around the world. The residue of atrazine due to its application in the fore-rotating crop maize has caused phytotoxicity to the following crop sweet potato in China. Bioaugmentation of atrazine-contaminated soil with atrazine-degrading strains is considered as the most potential method to remove atrazine from soil. Nevertheless, the feasibility of bioaugmentation and its effect on soil microbiome still need investigation. In this study, Paenarthrobacter sp. AT-5, an atrazine-degrading strain, was inoculated into agricultural soils contaminated with atrazine to investigate the bioaugmentation process and the reassembly of the soil microbiome. It was found that 95.9% of 5 mg kg−1 atrazine was removed from the soils when inoculated with strain AT-5 with 7 days, and the phytotoxicity of sweet potato caused by atrazine was significantly alleviated. qRT-PCR analysis revealed that the inoculated strain AT-5 survived well in the soils and maintained a relatively high abundance. The inoculation of strain AT-5 significantly affected the community structure of the soil microbiome, and the abundances of bacteria associated with atrazine degradation were improved.